Peningkatan Aktivitas dan Hasil Belajar dengan Model Pembelajaran Vak Berbantu Media Tongkat Tokoh - Rukmana, Winda; Hardjono, Nyoto; Aryana, Arlita (Journal of Education Action Research, 2018)
This research aims to improve the activity and the learning result by implementing teaching-learning model of VAK (Visual, Auditory, & Kinestethic) and figure stick media, This Classroom Action Research was conducted in the class 2 of SD Negeri Salatiga 06, Salatiga. The obtained data comprised the activity and the learning result, the teacher-observation result, and the student-observation result. The techniques of the data collection were observation, documentation, and test methods. This research was conducted in two cycles. Each cycle covers 4 (four) stages i.e. preparing, delivering, training, and evaluating. In this research, it can be concluded as successful if there is at least 80 percent of student total number gaining score ≥ 75. The result of this research shows that: (1) the activity scores of the students in the pre-cycle on class 3 is about 72 percent with the mean of 73.5 and the mastery level of student learning in the pre-cycle is about 74.5 percent with the mean of 76.5; (2) the activity scores of the students in the cycle I is about 70 percent with the mean of 76.2 and the cycle II is about 82.5 percent with the mean of 82.4; (3) the mastery level of student learning in the cycle I is about 72.5 percent with the mean of 78.15 and in the cycle II is about 83.5 percent with the mean of 85.25. From the data aforementioned, it clearly shows that the activity and the learning result did not achieve the target in the cycle I meaning that the indicators of success were not fulfilled, while the activity and the learning result achieved the target in the cycle II meaning that the indicators of success were fulfilled.